Effect Evaluation of Mental Nursing in Nursing of Young Cancer Patients Based on Big Data - Ren, Yuanpeng (Frontiers in Public Health, 2022)
The field of mental health nursing had always been special, dynamic, and flexible in terms of enhancing the individuals’ quality of life. Mental health nursing is all about caring individuals with mental health disorder with the aim of helping them recover from illness, thereby improving their living conditions. Health Education of mental nursing emphasizes on providing special care to patients and optimally fulfils the clinical outcomes of the patients. It has been widely accepted that mental illness negatively influences the well-being of individuals, irrespective of their age, origin, demography, social status, and economic status. Young patients diagnosed with cancer recorded that their lead a poor quality of life, as they undergo several physical and psychological needs, especially after the surgery and other cancer-related treatments. Thus, this study aims to examine the effect of mental health nursing in nursing young cancer patients, based on the big data. Thus, the study conducts longitudinal analysis of the data gathered from the young cancer patients, monitored by mental health nurse, with APN (Advance Practice Nurse) interventions. Results of the study stated that APN interventions positively impacted the physical as well as the psychological needs of the research subjects. Mental nursing interventions resulted in positive clinical outcomes of the patients.